The historical contribution of faith-based health providers in the Ecuadorian health system: an overview of the evidence. Issue 5 (4th July 2017) - Ullauri, Angelica; Olivier, Jill
ABSTRACT: Faith-based health providers (FBHPs) have historically shaped the national health system in Ecuador, yet there is little robust evidence of this role, or their current contribution to the national health system. This article situates FBHPs in the Ecuadorian health system, using secondary analyses of national health surveys to consider changes in contribution from 1998 to 2014, and synthesising this with secondary literature. The research confirms the important role that FBHPs have historically played in Ecuador, but also shows that their current role needs to be better understood if universalisation of health service coverage is to be achieved.